Dextromethorphan inhibits collagen and collagen-like cargo secretion to ameliorate lung fibrosis - Khan, Muzamil Majid; Galea, George; Jung, Juan; Zukowska, Joanna; Lauer, David; Tuechler, Nadine; Halavatyi, Aliaksandr; Tischer, Christian; Haberkant, Per; Stein, Frank; Jung, Ferris; Landry, Jonathan J. M.; et al. (Science translational medicine, 2024)
Excessive deposition of fibrillar collagen in the interstitial extracellular matrix (ECM) of human lung tissue causes fibrosis, which can ultimately lead to organ failure. Despite our understanding of the molecular mechanisms underlying the disease, no cure for pulmonary fibrosis has yet been found. We screened a drug library and found that dextromethorphan (DXM), a cough expectorant, reduced the amount of excess fibrillar collagen deposited in the ECM in cultured primary human lung fibroblasts, a bleomycin mouse model, and a cultured human precision-cut lung slice model of lung fibrosis. The reduced extracellular fibrillar collagen upon DXM treatment was due to reversible trafficking inhibition of collagen type I (COL1) in the endoplasmic reticulum (ER) in TANGO1- and HSP47-positive structures. Mass spectrometric analysis showed that DXM promoted hyperhydroxylation of proline and lysine residues on various collagens (COL1, COL3, COL4, COL5, COL7, and COL12) and latent transforming growth factor-β-binding protein (LTBP1 and LTBP2) peptides, coinciding with their secretion block. Additionally, proteome profiling of DXM-treated cells showed increased thermal stability of prolyl-hydroxylases P3H2, P3H3, P3H4, P4HA1, and P4HA2, suggesting a change in their activity. Transcriptome analysis of profibrotic stimulated primary human lung fibroblasts and human ex vivo lung slices after DXM treatment showed activation of an antifibrotic program through regulation of multiple pathways, including the MMP-ADAMTS axis, WNT signaling, and fibroblast-to-myofibroblast differentiation. Together, these data obtained from in vitro, in vivo, and ex vivo models of lung fibrogenesis show that DXM has the potential to limit fibrosis through inhibition of COL1 membrane trafficking in the ER.
Gesehen am 06.06.2025